PERSPEKTIF PEMIKIRAN SYED MUHAMMAD NAQUIB AL-ATTAS TENTANG PENDIDIKAN YANG BERADAB - ., Nuryamin (Jurnal Pendidikan Kreatif, 2022)
The purpose of this study is to describe the thoughts of Syed Muhammad Naquib al-Attas about civilized education. Syed Muhammad Naquib Al-Attas is one of the world leaders who has great attention to the development of educational thought in the Islamic world. In his view of education he consistently uses the term ta'dib. The word ta'dib is an infinitive vermood (masdar) from the root word "addaba" from Arabic which means giving manners or educating. Education is instilling and inculcation is an effort to absorb and internalize adab or educational values ​​in students. The absorption and internalization of material in the teaching and learning process in al-Attas' view is not just a transformation of knowledge as understood in the sense of teaching. However, the scope of the content of al-ta'dib material is the recognition and acknowledgment of reality as a form of emanation from the light of God. As the rays of God's light are imprinted in the order of existence consisting of a hierarchy according to its categories and levels, and that a person has his place in relation to reality and his capacity, physical, intellectual, and spiritual potential, that is ta'dib.